Factors Affecting Habitat Selection of Endangered Steppe Eagle (Aquila nipalensis) in Pakistan: Implications for Raptors Conservation - Shakeel Ahmad; Romaan Hayat Khattak; Liwei Teng; Khansa Kaneez; Zhensheng Liu (Diversity, 2022)
The steppe eagle (Aquila nipalensis) is an endangered migratory raptor species that migrates in winter to Pakistan and neighbouring countries. In Pakistan, the species migrate at the end of autumn and utilise different habitats across the country. Very little information is available about the species’ population status, distribution, and factors affecting its distribution in Pakistan. In the present study, we predicted the distribution of steppe eagles in Pakistan associated with different environmental variables. We used 149 presence points of the species from an online source (GBIF), published literature, and wildlife photographers. The MaxEnt analysis showed that highly suitable habitats were mostly present in Azad Jammu and Kashmir (AJK), federally administered areas and surrounding areas, southern areas of Sindh Province, and some parts of Khyber Pakhtunkhwa (KP) Province. In addition, some patches were also predicted by MaxEnt in Balochistan Province. Human population density (27.0%), chicken density (16.6%), temperature seasonality (11.1%), and rivers (10.3%) were identified as the main environmental factors that affect the habitat distribution of steppe eagle in Pakistan. Only a small percentage (2.62%) of the total Pakistan area was estimated to be a highly suitable area for steppe eagles, while 20.58% and 7.46% were identified as the least and moderately suitable areas, respectively. Conservation of identified habitats and mitigation of anthropogenic impacts to conserve this endangered eagle species are recommended for immediate and long-term conservation across Pakistan.